Implementasi IoT Sebagai Monitoring Sistem Pembayaran Uang Kos Berbasis Android - Tje Kevin Ariefaldi Ahmad (Jurnal Jaringan Telekomunikasi, 2020)
In a boarding house, there is a boarding house owner/manager who monitors and supervises. For tenants, you can make payments only when meeting with the boarding house owner/manager. In practice, boarding house owners are not always in the boarding house so there is a difficulty in monitoring the boarding payments for each room. The purpose of this final project is to make a tool to be able to monitor and manage boarding through the android smartphone media. In this system, boarding house owners can find out the payment status of each room and tenants can also find out the remaining rental time. This system is also installed with a doorlock solenoid which can be controlled by the boarding house owner via the Android application to open and close the boarding house door if the tenant has/has not made a payment. The process of sending data from the device installed in the room to the Android smartphone using an intermediary NodeMcu and sending data to Firebase so that the status can be monitored in realtime. In each room there is also a notification system in the form of an LED light. The LED light will give a warning about the remaining time of the boarding house rental. The conclusion in this final project, the application can perform monitoring realtime and tenants can control the solenoid with an average delay of 1m 68s. For sending data from hardware to the database, it has a delay of 0.2139673s which is quite good.